Study on the Effect of Exposure Time and Layer Thickness on Properties Of 3D Printing Parts Using DLP Method - Nguyen, Thanh Nhan; Nguyen, Huy Ninh; Tran, Vu Minh; Nguyen, Quang Huy; Le, Anh Tuan (Old Journal, 2019)
In recent years, 3D printing technology has been used in many industrial and home products. This paper investigates the effects of process parameters on the mechanical properties of 3D printing parts using photopolymer material. A DLP 3D printing machine was constructed for experimental researches and education. Two input control parameters: exposure time T(s) and layer thickness L(mm) were selected to investigate (i) the effects they have on various output data of tensile strength, bending strength and Shore A hardness and (ii) the effects of layer thickness to the shrinkage along Z axis. The results can be used in the process of choosing the suitable process parameters when printing 3D using the DLP method.